2012
DOI: 10.1073/pnas.1212677110
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the degenerate retina by photoreceptor transplantation

Abstract: Despite different aetiologies, age-related macular degeneration and most inherited retinal disorders culminate in the same final common pathway, the loss of photoreceptors. There are few treatments and none reverse the loss of vision. Photoreceptor replacement by transplantation is proposed as a broad treatment strategy applicable to all degenerations. Recently, we demonstrated restoration of vision following rod-photoreceptor transplantation into a mouse model of stationary night-blindness, raising the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
303
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 243 publications
(329 citation statements)
references
References 22 publications
18
303
1
7
Order By: Relevance
“…Reactive gliosis represents a barrier to successful stem cell‐based strategies in several neuropathological conditions 4, 5, 13, 37, 38. In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reactive gliosis represents a barrier to successful stem cell‐based strategies in several neuropathological conditions 4, 5, 13, 37, 38. In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive gliosis represents a barrier to successful stem cell‐based strategies in several neuropathological conditions 4, 5, 13, 37, 38. In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, a handful of studies have shown some restoration of vision in photoreceptor precursor cell (PPC) recipients, [6][7][8][9] though graft integration and survival remains too low to be clinically relevant. Short-term assessment in serial studies aimed at addressing these barriers currently relies on imaging, such as ophthalmoscopy and end point histology.…”
Section: Introductionmentioning
confidence: 99%